A case study of alpine and freestyle snowboard turn measurement - Saito, A.; Miyawaki, K.; Tsuji, N. (Proceedings of the 7th International Conference on Sport Sciences Research and Technology Support icSPORTS - Volume 1, 2019)
This study investigated the reaction force from the snow surface affecting a snowboarder during alpine snowboarding turns and freestyle snowboarding turns. Alpine snowboards and freestyle snowboards have different widths, shapes, flexes, and hardnesses. Snowboarder motions during turns using an alpine snowboard and freestyle snowboard differ. Therefore, analyzing the reaction force from the snow surface affecting the snowboarder gliding on an actual snow field is expected to be valuable for clarifying differences of snowboarder motions during alpine snowboarding turns and freestyle snowboarding turns. We developed a new measurement system for this study to measure the reaction force from the snow surface during snowboarding. Furthermore, we conducted experiments with a professional snowboarder gliding on an actual snow field using alpine and freestyle snowboards fitted with the measurement system. The center of pressure during alpine snowboarding showed that the right foot placed on the snowboard in the counter travel direction side was used mainly to press the snowboard edge during front-side turns. The left foot placed on the snowboard in the travel direction side was used mainly to press the snowboard edge during back-side turns. The center of pressure during freestyle snowboarding showed that both feet were used to press the snowboard edge.